Improving Job Satisfaction in Manufacturing Industries: Exploring Roles of Workplace Cold Violence, Abusive Supervision and Organizational Support - Nuraeni, Lenny; Wulandari, Ayu Ratna; Indriyani, Susi; Widaryo, Chandika Mahendra; Haribowo, Rio; Lubis, Fatimah Malini (Yayasan Gema Bina Nusantara, 2025)
In the manufacturing industry, employee job satisfaction not only has an impact on performance or contribution given to the company, but also has an impact on work discipline, loyalty and work quality. In types of industries with monotonous working conditions and uncomfortable working environments, job satisfaction is a challenge not only for company management but also for employees. This study aims to explore the role of workplace cold violence, abusive supervision and organizational support on employee job satisfaction, especially in the manufacturing industry. This study uses a qualitative research method, where researchers conduct a study of theories, literature and previous research results that discuss the relationship between all independent variables and dependent variables. The literature collected is scientific articles published in journals in the last seven years. Based on the results of the study and analysis conducted by researchers on the literature and the results of previous studies that discuss the relationship and influence of workplace cold violence, abusive supervision and organizational support variables on job satisfaction, it proves that there is a strong relationship between each independent variable and the dependent variable. Workplace cold violence and abusive supervision have been shown to have a negative effect on job satisfaction, while organizational support has been shown to have a positive effect on job satisfaction.